1035325 Hubungan Kehamilan Ganda, Riwayat Hipertensi, dan Obesitas dengan Kejadian Pre Eklampsia Pada Ibu Hamil - Maria Septiana (JURNAL KEBIDANAN AKADEMI KEBIDANAN BUDI MULIA PALEMBANG, 2019)
Abstract Pre Eklamsi is a syndrome characterized by increased blood pressure and proteinuria that appear in the second trimester of pregnancy which always recovers in the postnatal period. The formulation of the problem of this research is to find out whether there is a relationship between multiple pregnancy, history of hypertension and obesity simultaneously with the preeclampsia. The method used in this study is an analytic survey with cross sectional design and data check list. Variavel independent is a multiple pregnancy, a history of hypertension and obesity. The population in this study were all women who had been treated at the Palembang Bhayangkara Hospital in 2018. This study used secondary data obtained from the Bhayangkara Palembang Hospital Medical Record in 2018 with a sample of 97 respondents, it was found that there were preeclampsia as many as 41 respondents (42.3%) and those who did not experience preeclampsia were 56 respondents (57.7%). From the results of the analysis the Chi-Square statistical results obtained p value = 0,000, this shows that there is a significant relationship between multiple pregnancy, history of hypertension and obesity with theincidence of pre-eclampsia. Suggestions are given to Bhayangkara Hospital so that health workers provide health services by means of counseling and counseling to pregnant women regarding preeclampsia. Keywords: Multiple Pregnancy, History of Hypertension, Obesity and Preeclampsia